WRITING ATTITUDE AND EMOTIONAL INTELLIGENCE AS DETERMINANTS IN BOOSTING EFL LEARNERS’ WRITING PERFORMANCE - Elsya Agesty; Rita Inderawati; Eryansyah Eryansyah (University of Kuningan, 2021)
This study aimed to find out whether or not there was a significant correlation between students’ writing attitude, emotional intelligence and their writing performance, and the predictor variables and the criterion variable. It involved 121 students of the English Education Study Programs of Tridinanti, PGRI, and Muhammadiyah Universities in Palembang. The data were collected through the use of Writing Attitude Questionnaire, Emotional Intelligence Questionnaire and a writing test. The data were analyzed by using the Pearson Product Moment correlation coeficient and partial correlation analysis. The results showed that there were significant correlations in a row of the writing attitude and writing performance with r-obtained was 0.342. There results showed there were significant correlations of emotional intelligence and writing performance because the value of.028 with the correlation coefficient of .140. and the results of the partial correlation showed that writing attitude, emotional intelligence, and writing performance had a significant correlation with r value of .280 and p-value of <.001.